Multiracial identity development and the impact of race-oriented student services - Roque, Margaret (Kansas State University, 2013)
Multiracial identity development has been a topic of study that has slowly begun to grow interest in academia. While it is important to acknowledge the process of multiracial identity development in and of itself, it is also essential to understand how this development is influenced by different ecological factors in higher education, such as when and where a multiracial student may encounter instances of marginalization, as well as instances of mattering. One of the more prominent facets of this ecology is race-oriented student services, which can provide either a space in which multiracial students feel marginalized, or one in which they feel that they matter. This report will examine multiracial identity development and why it is needed in order to better understand multiracial students’ needs, as well as how race-oriented student services affect development and expression of their identity.
Keywords: Multiracial identity; Biracial identity; Race-oriented student services; Higher Education (0745); Higher Education Administration (0446)